The Impact of Capital Structure on Corporate Financial Performance: A Case Study of Alibaba and E-commerce Industry - Liu Siqi (SHS Web of Conferences)
The composition ratio of different capital sources in a company forms different financing structures among companies, and at the same time produces different financing costs and economic benefits, which have different impacts on the company’s financial performance. Corporate capital structures are becoming more and more important as the e-commerce sector develops quickly. Through in-depth analysis of the capital structure of Alibaba and related enterprises in the industry, this paper discusses the influence mechanism of different sources of capital and capital structure on financial performance. Research indicates that a sensible capital structure can enhance financial performance by lowering borrowing costs and optimizing the use of available money. On the contrary, improper capital structure may lead to increased financial risk and decreased profitability. This paper aims to provide useful reference for e-commerce corporations to optimize capital structure and enhance financial performance and promote the sustainable and healthy development of Alibaba and e-commerce industry.